The Influence of School Context on Elementary Students’ Reading Interest: A Descriptive Study in Cirebon City - Febriani, Nadya (CV. Akademi Merdeka, 2024)
This study aims to examine the influence of school context on the reading interest of elementary school students in Cirebon City. The school context refers to teacher support, the availability of literacy facilities (particularly libraries), and the implementation of school-based literacy programs. A quantitative descriptive approach was employed, using a reading interest questionnaire administered to grade II and III students across four public elementary schools. Data were analyzed through validity and reliability tests, descriptive statistics, and one-way ANOVA to identify differences in reading interest among schools. The findings reveal a significant influence of school context on students' reading interest, with schools demonstrating stronger literacy support consistently reporting higher engagement levels. These results underscore the need for context-sensitive literacy strategies, including active teacher involvement, access to engaging reading materials, and a sustained culture of reading. The study offers actionable insights for policymakers and educators in designing effective and sustainable literacy interventions in primary education.